Factors affecting stone free rate of primary percutaneous nephrolithotomy on staghorn calculi: a single center experience of 15 years [version 2; referees: 2 approved] - Widi Atmoko; Ponco Birowo; Nur Rasyid (F1000Research, 2016)
Objectives: Percutaneous nephrolithotomy on staghorn calculi is challenging for urologists because it is difficult to remove all of the stones. The purpose of this study was to evaluate the associated factors of stone-free rate after primary percutaneous nephrolithotomy on staghorn calculi in a large series of patients at a single, tertiary referral, endourologic stone center. Methods: We collected data from medical record between January 2000 and December 2015. A total of 345 primary percutaneous nephrolithotomy procedures were performed for patients with staghorn calculi. This study included both and made no distinction between partial and complete staghorn calculi. Stone-free is defined as the absence of residual stones after undergoing percutaneous nephrolithotomy for the first time. Significant factors from univariate analysis that correlated with stone-free rate after primary percutaneous nephrolithotomy of staghorn stone were further analyzed using multivariate regression analysis. Results: The mean patient age was 52.23±10.38 years. The stone-free rate of percutaneous nephrolithotomy monotherapy was 62.6%. The mean operating time was 79.55±34.46 minutes. The mean length of stay in hospital was 4.29±3.00 days. Using the chi-square test, history of ipsilateral open renal stone surgery (p = 0.01), stone burden (p = < 0.001), and type of anesthesia (p = 0.04) had a significant impact on the stone-free. From multivariate analysis, the history of ipsilateral open renal stone surgery [OR 0.48; 95% CI 0.28-0.81; p 0.01] and the stone burden [OR 0.28; 95% CI 0.18-0.45; p 0.00] were significant independent risk factors for stone-free.